2021
DOI: 10.1002/mus.27191
|View full text |Cite
|
Sign up to set email alerts
|

A novel exercise testing algorithm to diagnose mitochondrial myopathy

Abstract: Introduction Oxygen uptake efficiency slope (OUES) is a noninvasive cardiopulmonary exercise testing (CPET) measurement based on oxygen uptake (V˙O2) and minute ventilation (V˙E) and is a marker of the efficiency of oxygen utilization by the body. However, it has not been studied in mitochondrial disorders. We explored noninvasive CPET parameters, including OUES, as a way to reliably diagnose mitochondrial myopathy. Methods We performed cycle ergometer maximal exercise testing on definite and suspected mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Our finding that the global pattern of exercise responses, which included impaired oxygen utilization, increased ventilation, and hyperdynamic heart rate, parallels CPET findings seen in those with mitochondrial myopathies [8,15,20] also contributes to existing literature regarding physical function after the ICU. Muscle mitochondrial dysfunction occurs early in critical illness and sepsis [21], and it is strongly linked to survival.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our finding that the global pattern of exercise responses, which included impaired oxygen utilization, increased ventilation, and hyperdynamic heart rate, parallels CPET findings seen in those with mitochondrial myopathies [8,15,20] also contributes to existing literature regarding physical function after the ICU. Muscle mitochondrial dysfunction occurs early in critical illness and sepsis [21], and it is strongly linked to survival.…”
Section: Discussionsupporting
confidence: 72%
“…No participants had ventilatory or gas exchange limitations to exercise nor exercise-induced ischemia. Participants did, however, have a pattern of low oxygen pulse, elevated chronotropic index, low VO 2 -work rate slope, and prolonged VO 2 recovery halftime, indicating impaired oxygen utilization with a hyperdynamic heart rate response (Table 2), a physiologic pattern that mirrors responses seen in patients with mitochondrial myopathies [8,15,20]. VO 2 -work rate slope and VO 2 recovery half-time were strongly correlated with both VO 2Peak and 6MWT distance (Figs.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This suggests that CPET should be used in conjunction with other diagnostic investigations; or used instead to monitor progress following exercise interventions. Despite these limitations, some variables measured during CPET could be used to establish the suspicion of primary mitochondrial myopathies, although it would warrant further testing 54–56,99,102 …”
Section: Exercise Testing In Iememmentioning
confidence: 99%
“…98 A recent study reported these patients have a lower ratio of oxygen uptake to power output (work) slope, highlighting a reduced ability to utilise oxygen to attain a particular workload compared to control subjects. 54,56,[99][100][101][102][103] Similar to McArdle disease and LC-FAOD, patients with primary mitochondrial myopathies appear to have significantly lower exercise capacity than their healthy peers, though the evidence in children and adolescents remains quite limited (see Table 4). [99][100][101][102] Within the mitochondrial cohort there is very wide variability in exercise capacity, with some patients not meeting the minimum VO 2 threshold for ADLs (15 mL/ kg/min for women, 18 mL/kg/min for men) 2,104 and others achieving VO 2 peak greater than 90% of predicted.…”
Section: Cpet In Iememmentioning
confidence: 99%